Description Of Teraupeutic Communication Of Nurses At Santa Elisabeth Hospital Medan: Teraupeutic Communication - Khatlyn Theopani Dongoran; Karo, Mestiana; Simorangkir , Lindawati (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Therapeutic communication is communication designed, planned for therapeutic purposes in fostering relationships between nurses and patients so that they can adapt to stress, overcome psychological disorders experienced by patients, so that they can relieve and make patients feel very comfortable, which in turn accelerates the patient's healing process. starting from the pre-interaction stage, the work stage and the termination stage by providing accurate information to that they can assist patients in overcoming problems during the treatment stage. This study aims to describe the therapeutic communication of nurses at Santa Elisabeth Hospital Medan. Methods: The research design used is a descriptive study with a cross-sectional approach with 7,772 population of inpatients. The instrument used is nurse therapeutic communication variable questionnaire sheet. The sampling technique is purposive sampling with a total sample of 94 respondents Results: The study results found that the nurse's therapeutic communication at Santa Elisabeth Hospital Medan. The pre-interaction stage is in very good category 87%, the work stage is 90%, and the termination stage is in good category 65%. Conclusions: Based on the results obtained, it can be concluded that nurse therapeutic communication is very well carried out by nurses when carrying out nursing actions and providing nursing care to patients, and remembering more about introducing their identity to clients, and remembering to make contracts for the next meeting. It is hoped that this research can be input for hospitals and nurses continue to provide good therapeutic communication to patients, for health institutions to reference material in therapeutic communication courses.